Differences in Learning Outcomes and Critical Thinking Skills of Students Taught with Discovery Learning Model and Probleam Based Learning Assisted with Powerpoint Media on Acid-Base Material - Sitompul, De Enovani; Simorangkir, Murniaty (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
Abstract: Differences in Learning Outcomes and Critical Thinking Skills of Students Taught with Discovery Learning Model and Probleam Based Learning Assisted by Powerpoint Media on Acid-Base Material. This study aims to examine the learning outcomes and critical thinking skills of students instructed in problem-based learning with PowerPoint presentations on acid-base topic versus the discovery learning model. We refer to this type of research as a quasi-experiment. Every pupil in class XI IPA SMA S Markus Medan and samples from classes The study's population consisted of XI IPA 1 and XI IPA 2, who were selected using total sampling. The study's conclusions showed that students' learning outcomes and ways of thinking differed depending on whether they were taught using DL or PBL approaches. In the first experimental class, students' average learning result was 80.00, while the average for individuals in experimental class II was 76.56. The students in the Experiment I class (79.88) and the Experiment II class (76.63) are then shown for their mean critical thinking scores. The correlation test between learning results and critical thinking abilities among students taught using the DL model is 0.667, whereas students taught using the PBL paradigm has a 0.365 correlation test.Keywords: Discovery Learning, PowerPoint, learning outcomes, problem-based learning, and critical thinking skills.DOI: 10.23960/jppk.30025